A Small Box in the Heart - (:unkn) unknown (My University, 2016)
From the enchanted confines of her Turkish grandmother’s home, Maryam Abdel Fatah recollects the phases of her life, growing up in the tumultuous environment of Egypt in the late 1970s and early 1980s. Although the historical time frame of the novel takes us back some decades before the Egyptian revolution of 2011, it speaks to many of the issues and concerns that brought about that revolt—and indeed—to some of the broader concerns underlying the so-called Arab Spring. The story of Maryam’s young life details the tragic impact upon individuals of the lack of personal and political freedoms, and of an economy that provides youth with little hope for work and stable futures. Through its shifting and poetic prose, it also examines a woman’s deep-seated longing for meaningful connections with others in the same boat.
Keywords: women; fiction; Egypt